Ferrielectric liquid crystal subphase studied by polarized Fourier-transform infrared spectroscopy - VIJ, JAGDISH KUMAR; PANARIN, YURI PETROVICH (American Physical Society, 2000)
IR dichroism and the structure of a homogeneously aligned cell of a chiral smectic antiferroelectric liquid crystal (R)-1-methylheptyl 4-(4?-dodecyloxybiphenyl-4-ylcarbonyloxy)-3-fluorobenzoate [with acronym (R)-12OF1M7] in a ferrielectric subphase in the temperature range between the antiferroelectric phase (also referred to as Fi2) and the smectic-C*(SmC*) phase are studied using polarized Fourier transform IR spectroscopy. The polarization dependencies of the absorbance for several characteristic bands are quantitatively analyzed for different stages of the electrically induced structural transformations in the sample, including the helix unwinding and the phase transition from the ferriphase to the SmC* phase. A qualitative similarity of the voltage dependence of the normalized angular shift of the IR absorbance profile for the ?chiral? carbonyl band to that of the normalized macroscopic polarization is found. The voltage dependent dichroic properties of the sample are analyzed in terms of the molecular structure and unwinding of the helical structure under an external electric field. The rotational orientational biasing of the carbonyl groups around the long molecular axis is confirmed by the spectral data. The analysis of IR dichroic data for the field induced SmC* phase is used to determine the rotational orientational distributions for the carbonyl groups.
PUBLISHED
Keywords: Condensed matter physics; antiferroelectric liquid crystal